Formação continuada docente: qualificação profissional de alunos ludovicenses com deficiência - SILVA , Clediane Alencar da (2021)
The continuing education is one of the most researched and debated theme, as the educational demand requires new educational practices and a new teaching profile for each area of acting. However, the predominant model in educational circles corresponds to the classic of continuing education, based on the updating or recycling of initial formation. Based on this perspective, the continuing teacher education should also be discussed and improved in the various fields of acting, as Professional Education, where the teacher must have specific knowledge to work in this modality of teaching, so that he can qualify students with deficiency in technical and professional courses. This research was configured as field research, descriptive and documentary, with a quantitative-qualitative approach, whose main objective was to analyze how happened the process of continuing education of teachers from the National Service for Commercial Learning and the National Service for Industrial Learning for the professional qualification of students with visual and/or intellectual deficiency in São Luís. Participated 4 teachers from the first institution and 5 from the second, all male, with an average age of 41 years. Were used official and unofficial documents, as well as semi-structured interviews with two blocks of questions. About to continuing teacher education, it was found that some did not know how to answer how it happened, others stated that it happens periodically, in person and EaD form, being that, the acquired knowledge helped to qualify students with deficiency. It was also found that all teachers received continued training, however, the majority, in the technical and professional areas. About the training to work with students with disabilities, the data analyzed showed that most of these teachers did not know if they occurred or how they occurred, and about the frequency of training received, they took place annually. Concluded that, although the two institutions researched offer continuing education to their teachers, they didn’t contemplate their aspiration and difficulties in the classroom everyday when working with human diversity, to lack of more specific formation for the inclusion of people with visual and/or intellectual deficiency, especially in the job Market as well as a lack of knowledge that speaks and is contextualized with the reality of the professional education.